Analisis Penerimaan Pengguna terhadap Claude AI sebagai Virtual Coworker Menggunakan Model TAM (Technology Acceptance Model) - Guidio Leonarde Ginting; Surya Darma Nasution (Graha Mitra Edukasi, 2026)
The acceptance of artificial intelligence technology in the workplace has become a primary concern in Indonesia's digital transformation era. Claude AI, a generative AI assistant developed by Anthropic, demonstrates significant potential as a virtual coworker supporting work productivity. This study analyzes Indonesian professional users' acceptance of Claude AI using the Technology Acceptance Model (TAM) framework (Davis, 1989), covering Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention (BI). A quantitative survey method was applied to 120 professional respondents in Indonesia. Regression analysis results show all hypotheses were accepted (p < 0.05): PEOU positively affects PU (β = 0.412), PU affects ATU (β = 0.387), PEOU directly affects ATU (β = 0.298), and ATU is the strongest predictor of BI (β = 0.521). These findings indicate that ease of use and perceived usefulness of Claude AI jointly contribute to positive behavioral intention among Indonesian professionals